Conversational repair, gender, and interactional competence in an Indonesian EFL classroom: Insights and implications - Utami, Almira (ELT Forum: Journal of English Language Teaching, 2025)
This article provides a qualitative examination of conversational repair in an Indonesian EFL (English as a Foreign Language) classroom, focusing on how gender differences in initiating repair strategies are indicative of the EFL learners’ interactional competence (IC). Based on data from a case study approach involving ten adult students, five male and five female students, in an English course class, the article contributes to an in-depth insight into how male and female students handle communication problems. The results show that there are patterns: female students tend to utilize “weaker” or less specific repair initiators, suggesting a pragmatic orientation to politeness, as well as a collaborative approach to the identification of problems. In contrast, male students mainly employ "stronger" and more direct techniques, including a higher frequency of direct "correction”, hinting at a more assertive interactional style focusing on a prompt resolution of the detected issue. According to the findings, gendered preferences of repair initiations have some direct implications for various aspects of interactional competence, both of learning the language itself and of dealing with the pragmatic dimensions of talk. The findings have important implications for EFL pedagogy regarding the groundwork of explicit instruction on different types of repair strategies and gendered communicative styles to promote more equitable and effective classroom interactions and greater interactional competence in general.